P727 Quality of life and disease activity in children and adolescents with inflammatory bowel disease. (25th January 2019) - Aloi, M; Carloni, E; Palmacci, F; Distante, M; Catassi, G; D'Arcangelo, G; Cucchiara, S; ,
Abstract: Background: inflammatory bowel diseases (IBD) have a major impact on quality of life (QoL). Clinical scores used in routine clinical practice do not take into account patients and families' perceptions of social lives. The main objective of this study was to evaluate QoL perceived by patients and their parents and to define the concordance among patients, parents, and physician' perception. As secondary outcomes, we aimed at assessing the impact of disease duration on QoL and the effectiveness of a psychological therapy Methods: All consecutive children with IBD and their parents followed-up at the Pediatric Gastroenterology and Endoscopy Unit of the Department of Pediatrics of Sapienza University of Rome were recruited from June 2017 to June 2018. At each routine visit, disease activity was evaluated by the treating physician by the Physician Global Assessment (PGA). Two scores for measuring health-related QoL were administered to all patients: the Pediatric Quality of Life Inventory (PedsQL) and the IMPACT III, a 35-item self-administered questionnaire with a total score ranging from 35 (poor) to 175 (best). One or both parents completed the IMPACT III questionnaire. A subgroup of patients and their families started a psychological support Results: One hundred twenty-one children and their parents entered the study. Mean IMPACT III was 136.55 ± 19.06 for patients and 126.59 ± 21.26 for parents ( p < 0.0001), regardless of disease activity. Parents had worse perceptions mainly in the emotional and social domains, compared with their children ( p < 0.0001 and p < 0.001, respectively). Disease activity evaluation was similar between patients and physician, with a negative correlation between PGA and IMPACT III ( r = 0.4971; p < 0.0001). Patients with moderate/severe disease had a worse perception of QoL compared with those with an inactive and mild disease ( p < 0.0001). No statistically significant difference was found based on disease duration (less or more than 1 year) (IMPACT III patients 140 ± 17.46 vs 135.06 ± 19.77; p = 0.106; parents 130.97 ± 20.7 vs. 124.75 ± 21.34; p = 0.07). Twenty patients and their families started a psychological therapy. No significant difference was found in the perception of QoL following the psychotherapy (IMPACT III patients 134.55 ± 17.73 and 140.1 ± 16.41; p = 0.162. Parents 123.67 ± 20.49 vs. 130.74 ± 22.74; p = 0.16). Conclusions: Our study suggests that parents of children with IBD have a significantly lower perception of QoL compared with their children, independent of disease duration and activity. Children with a severe disease have a poor QoL perception, which is correlated with physician disease assessment. Psychological support was not correlated with a significant QoL improvement, probably due to the small sample size and the short study follow-up.